DEVELOPMENT OF A STUDENT WORKSHEET FOR ELECTRIC CIRCUIT LEARNING BASED ON AN ARAKAN SAHUR MINIATURE IN A LOCAL CULTURAL CONTEXT INTEGRATED WITH THE STEM APPROACH - Kelvin Kelvin; Haerul Pathoni; Jules Nurhatmi (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2026)
This study aims to develop and examine the feasibility of a student worksheet for teaching electric circuits based on the Arakan Sahur miniature integrated with the STEM approach. The research employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate), limited to the Develop stage. The subjects involved two expert validators, one physics teacher, and 12 Grade XII students of SMAN 9 Kota Jambi in a limited trial. Data were collected through interviews and questionnaires, including expert validation sheets and practitioner and student response questionnaires, and analyzed using descriptive qualitative and quantitative techniques with a Likert scale and percentage calculations. The validation results showed that the student worksheet achieved a very good category in both material and media aspects after revision. Student responses indicated very high levels of attractiveness, while practitioner responses reached a very good category in all assessed aspects. The integration of science, technology, engineering, and mathematics through the local cultural context of Arakan Sahur contributes to making electric circuit learning more contextual, meaningful, and capable of enhancing students’ conceptual understanding and problem-solving skills in physics education.